Sistem Prevensi School Violence di Madura Berbasis Galtung Conflict Triangle - Ridwan, Auliya (Program Pascasarjana UIN Sunan Ampel Surabaya, 2009)
School violence may be understood as the threat or use of physical force with the intention to cause physical injury, damage of property or intimidation of another person at school. School violence is also violence that happens outside school as a result of a social interaction among the students. With regards to their prevention, many theories and propositions have been introduced including that of Conflict Triangle theory by Johan Galtung. This paper is aimed at analyzing school violence in Madura by using this theory as a general framework of analysis. The paper will begin by providing a general overview of both the theory and the so-called carok tradition of Madura; a tradition of self-defense using traditional blade which often involves killing. Upon highlighting school violence in this island, the paper will then move on by suggesting that in order to delegitimize this violence, one must speak of preventive programs at practical level, and of deconstructing the cultural strength of carok tradition at the discursive one. We assume that once the carok tradition is being deconstructed, one would loose the cultural legitimacy of committing violence. In Madura violence is often legitimated by the culture and tradition of carok. To eradicate violence is therefore to get rid of carok tradition in the first place.